THE INFLUENCE OF PANCASILA EDUCATION LEARNING ON INCREASING SOCIAL AWARENESS AND NATIONALISM OF STUDENTS - Nur Hidayat (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to determine the influence of Pancasila Education learning on increasing students' social awareness and nationalism. Using a quantitative approach with a survey method, this study involved 100 high school students who had participated in Pancasila Education learning. The instrument used was a closed questionnaire that was validated and tested for reliability. The results of the study show that Pancasila Education learning has a positive and significant influence on both variables, namely social awareness and nationalism. Students who participated in learning with an interactive and contextual approach showed a higher level of empathy, social concern, and a sense of love for the homeland. Regression analysis shows that Pancasila Education learning contributes 42.3% to social awareness and 48.1% to student nationalism. These findings confirm that Pancasila Education not only functions as an instrument of normative knowledge, but also as a medium for the formation of social character and national identity. Therefore, a more applicable and reflective learning approach needs to be developed so that Pancasila values can be internalized more optimally in students' lives.